2015
DOI: 10.18203/issn.2454-2156.intjscirep20150217
|View full text |Cite
|
Sign up to set email alerts
|

Objective Structured Practical Examination: our experience in Pharmacology at Goa Medical College, Bambolim-Goa, India

Abstract: Background: Practical examination is an important component of evaluation in the medical curriculum. OSPE (objective structured practical examination) pattern has structured questions with marks for each point and all the objectives of teaching-learning can be tested and assigned the desired weightage. Methods: The evaluation was done for 146 II MBBS students in Pharmacology. Every student had to spend two minutes each for dosage form (DF) and drug advice (DA) at their respective stations. All the students had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 7 publications
2
11
0
Order By: Relevance
“…[ 16 ] The students unhappiness with time allotted has also been reported in an earlier study by Chandelkar et al . [ 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 16 ] The students unhappiness with time allotted has also been reported in an earlier study by Chandelkar et al . [ 17 ]…”
Section: Discussionmentioning
confidence: 99%
“…[15] In another study by Chandelkar et al ., it was found that all the students accepted OSPE because it helped them improve their practical skills and application in pharmacology. [16] Results of another study indicated better effect of objective structured assessment of technical skills on learning. [17]…”
Section: Discussionmentioning
confidence: 99%
“…A similar opinion was noted in a study by Chandelkar et al 8 81% of students felt OSPE was well structured, relevant and uniformity in evaluation are the documented advantages of this method compered to TPE. 8 The correlation between performance scores of OSPE and TPE were (r=0.48) statistically significant (P< 0.01). This was in accordance to a study by Rajan et al, where significant (P<0.05) improvement was observed in the performance scores obtained in OSPE as compared to TPE (Table 1).…”
Section: Discussionmentioning
confidence: 85%
“…This was in tandem with a study by Chandelkar et al, it was found that all the students accepted OSPE helped them improve their practical skills. 8 Examination is well known source of stress and anxiety and OSPE in particular was considered with quite minimum stress levels in our study. These findings were similar to a study by Wadde et al, probably this could be possibly due to least or indirect interaction with the examiners as well as students undergoing limited number of stations.…”
Section: Discussionmentioning
confidence: 99%